2020
DOI: 10.3389/fonc.2020.01226
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Polycomb Repressive Complex-2 in Mantle Cell Lymphoma Confers Growth Advantage by Epigenetic Suppression of cdkn2b

Abstract: The polycomb repressive complex 2 (PRC2) maintains the transcriptional repression of target genes through its catalytic component enhancer of zeste homolog 2 (EZH2). Through modulating critical gene expression, EZH2 also plays a role in cancer development and progression by promoting cancer cell survival and invasion. Mutations in EZH2 are prevalent in certain B-cell lymphoma subtypes such as diffuse large cell lymphoma and follicular lymphoma; while no EZH2 mutation has been reported in the mantle cell lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Polycomb repressive complex 2 (PRC2) comprises EZH2, EED and SUZ12, among which, EZH2 is the only active subunit with a critical role. [17][18][19] The EZH2 catalytic SET domain catalysing histone 3 lysine 27 tri-methylation (H3K27me3) is reported to bind and silence specific tumour suppressor genes. 20,21 Earlier, Kamijo and co-workers demonstrated upregulation of EZH2 in NB in association with poorer prognosis and overall survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polycomb repressive complex 2 (PRC2) comprises EZH2, EED and SUZ12, among which, EZH2 is the only active subunit with a critical role. [17][18][19] The EZH2 catalytic SET domain catalysing histone 3 lysine 27 tri-methylation (H3K27me3) is reported to bind and silence specific tumour suppressor genes. 20,21 Earlier, Kamijo and co-workers demonstrated upregulation of EZH2 in NB in association with poorer prognosis and overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…Polycomb repressive complex 2 (PRC2) comprises EZH2 , EED and SUZ12 , among which, EZH2 is the only active subunit with a critical role 17‐19 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…EZH2 mutation has not been identified in MCL patient samples or MCL cell lines [32,61], although PRC2/EZH2 complex overexpression has been reported in MCL cell lines [77,78]. The work of Demosthenous et al showed that deregulation of PRC2/EZH2 in MCL cell lines mediates epigenetic silencing of the CDKN2B CDK inhibitor gene to promote MCL cell proliferation and survival [77]. In addition, it has been shown that EZH2 overexpression in MCL cell lines and primary cells facilitates recruitment of the DNA methylation machinery, enabling more stable and long-term repression of HOX genes [78].…”
Section: Histone Methylationmentioning
confidence: 98%
“…In addition to mutation, other genetic lesions affecting EZH2, including chromosomal gain or loss and DNA hypermethylation, have been identified in B-cell malignancies [100,117]. EZH2 mutation has not been identified in MCL patient samples or MCL cell lines [32,61], although PRC2/EZH2 complex overexpression has been reported in MCL cell lines [77,78]. The work of Demosthenous et al showed that deregulation of PRC2/EZH2 in MCL cell lines mediates epigenetic silencing of the CDKN2B CDK inhibitor gene to promote MCL cell proliferation and survival [77].…”
Section: Histone Methylationmentioning
confidence: 99%
“…EZH2 gene mutations are uncommon in MCL, but a deregulated expression of EZH2 and chromodomain-containing proteins, such as EED and SUZ12, has been reported in MCL. 83 …”
Section: Efficacy Of Novel Agentsmentioning
confidence: 99%